2010
DOI: 10.3748/wjg.v16.i27.3371
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soy saponin on the growth of human colon cancer cells

Abstract: Soy saponin may be effective in preventing colon cancer by affecting cell morphology, cell proliferation enzymes, and cell growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 19 publications
2
26
0
Order By: Relevance
“…Soyasaponin III followed a similar pattern with reductions of: 18.2, 32.7, and 40.0%. Depending on the soyasaponin, the percent reductions in PKC activity of this study are close to those of the previously mentioned studies (Tsai et al, 2010;Kim et al, 2004;Oh & Sung, 2001) which used soyasaponin mixtures. Soyasaponin I reduction was less than the reported values in these studies when used at the same concentrations, but soyasaponin III had a greater reduction at the 0.6 mg/ml concentration compared to mixtures of soyasaponins at that same concentration.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Soyasaponin III followed a similar pattern with reductions of: 18.2, 32.7, and 40.0%. Depending on the soyasaponin, the percent reductions in PKC activity of this study are close to those of the previously mentioned studies (Tsai et al, 2010;Kim et al, 2004;Oh & Sung, 2001) which used soyasaponin mixtures. Soyasaponin I reduction was less than the reported values in these studies when used at the same concentrations, but soyasaponin III had a greater reduction at the 0.6 mg/ml concentration compared to mixtures of soyasaponins at that same concentration.…”
Section: Discussionsupporting
confidence: 87%
“…At the highest concentrations of soyasaponin and soyasapogenol B, complete deformation of Caco-2 cells was observed ( Figure 6). Similar results were seen by Tsai et al (2010). Changes in cell morphology are suggestive that soyasaponins may be binding to or inserting into the cell membrane.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…For instance, saponins appear to inhibit the infectivity of the AIDS virus (Nakashima et al 1989;Vlietinck et al 1998) and the herpes simplex virus type 1 (Hayashi et al 1997). Soyasaponins are reported to be hepatoprotective (Kinjo et al 2003) and have also shown a preventive effect on the growth of human colon cancer cells (Tsai et al 2010). The chemical structure significantly influences the saponins bioactivity; thus, individual soyasaponin I exhibits lipid peroxidation inhibitory effects in vitro, antiinflammatory properties in mice with TNBS-induced colitis (Lee et al 2010), and potentially reduces metastatic ability of cancer cells (Chang et al 2006).…”
Section: Saponinsmentioning
confidence: 99%
“…Epidemiological studies have shown that the association between the consumption of soy or soy products with reduced risk of colorectal cancer 9-11 . Soybeans contain a variety of phytochemicals, which demonstrated anticancer activity, including isoflavone 12 , protease inhibitor 13 , saponin 14, 15 , lectin 16 , and more recently lunasin, a novel cancer preventive seed peptide bioactive peptides involved in the preventive and therapy of cancer 6, [16][17][18] . This study explores the use of Indonesian native plants, which was Grobogan soybean variety.…”
Section: Introductionmentioning
confidence: 99%